Assessment of rock Slope Stability on Shaqlawa – qoysinjaq Road, North Eastern Iraq by using kinematic analysis - Salam Subhi Hameed; Amera Ismail Hussein; Ayyed Hussein Ward (Tikrit Journal of Pure Science)
This study aims to assess the stability of the rock slopes on both sides of the road linking (Shaqlawa- qoysinjaq) to some of the exposed geological formations within the northeastern limb of the Safin anticline (Qamchuqa, Bakhma, Shiranish), where (6) stations were selected and a classification was made. An engineering description of the rock layers through a comprehensive survey of the study area, the results of the kinematic analysis by the kinematic analysis software (DIPS) showed that the possible percentage failures were represented by rock toppling (83.33%), planar sliding by (58.33%) and then wedge sliding by percentage (83.34%), By studying the factors affecting the stability of slopes in the region, it was found that the main factor causing the failures is the result of cutting the fold for the purpose of road construction, in addition to the structural and lithological factors.